Pengembangan Virtual Tour 360 Interaktif untuk Meningkatkan Pengunjung Wisata di Pulau Mubut - Agung Riyadi; Fadli Suandi; Riwinoto Riwinoto; Dwi Ely Kurniawan; Ridho Hafiedz; Wirabuana Sakti; Dian Nurdiansyah; Atalarik Ramli; Kerobaganet Kerobaganet; Bisma Khairunnas (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Mubut Island, which is located on Galang Island, Riau Archipelago, is one of the beauties of tourism in Indonesia. Information about the Mubut Island Tourism Object is not widely available in digital media, so that the delivery of information about Mubut Island is not optimal. Therefore, the purpose of this service is to provide information on Mubut Beach attractions using Virtual Reality (VR) technology. In addition to presenting the natural beauty of Mubut Island as a whole with 360 videos, this VR application also provides tourist education on visiting Mubut Island. This VR application was socialized at an exhibition in a mall in Batam to get VR user feedback. From the results of the socialization, it was found that 120 respondents assessed the benefits of this application and got a Likert index of 83.75% included in the useful category for potential tourists.